Portal Cavernoma Cholangiopathy: Histologic Features and Differential Diagnosis. Issue 3 (24th October 2018) - Pittman, Meredith E; Kierans, Andrea S; Rao, Deepthi; Yantiss, Rhonda K; Samstein, Benjamin; Jessurun, Jose
Abstract: Objectives: Portal cavernoma cholangiopathy (formerly portal biliopathy) is a type of biliary injury that occurs in association with a portal vein thrombus or cavernoma. Although the radiographic features of portal cavernoma cholangiopathy have been enumerated in the literature, its histologic features have not been described in detail. Methods: We describe the histologic findings in liver specimens from three patients with radiologically confirmed portal cavernoma cholangiopathy. Results: Of the three patients, one underwent surgical resection due to a clinical suspicion for cholangiocarcinoma, one had a liver biopsy sample obtained for evaluation of possible cirrhosis, and one had a clinically suspicious "hilar mass" at the time of orthotopic liver transplant. Histologic features common among the three liver specimens included portal venous abnormalities, where the portal veins were obliterated or small relative to the portal tract size, and obstructive biliary changes, such as ductular reaction and reactive epithelial atypia accompanied by a mixed inflammatory cell infiltrate with neutrophils. Conclusions: This case series provides clinicopathologic characteristics of portal cavernoma cholangiopathy. Histologic changes are reminiscent of hepatoportal sclerosis and/or bile duct obstruction. Attention to portal veins can provide helpful diagnostic clues, especially when biopsy samples are obtained from patients with a known portal vein thrombus or cavernoma.